2003
DOI: 10.1074/jbc.m212467200
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy Is Required for Multicellular Development of the Social Amoeba Dictyostelium discoideum

Abstract: Macroautophagy is a mechanism employed by eukaryotic cells to recycle non-essential cellular components during starvation, differentiation, and development. Two conjugation reactions related to ubiquitination are essential for autophagy: Apg12p conjugation to Apg5p, and Apg8p conjugation to the lipid phosphatidylethanolamine. These reactions require the action of the E1-like enzyme, Apg7p, and the E2-like enzymes, Apg3p and Apg10p. In Dictyostelium, development is induced by starvation, conditions under which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
204
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(221 citation statements)
references
References 44 publications
15
204
0
2
Order By: Relevance
“…In S. cerevisiae, autophagy mutants are defective in spore formation, 8 while autophagy mutants of D. discoideum are defective in normal multicellular developmental processes such as aggregation formation and fruiting body formation. 9 Premature death from the third larval to pupal stages was reported in D. melanogaster mutants. 10,49 Finally, dauer formation is abnormal in Caenorhabditis elegans autophagy mutants.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. cerevisiae, autophagy mutants are defective in spore formation, 8 while autophagy mutants of D. discoideum are defective in normal multicellular developmental processes such as aggregation formation and fruiting body formation. 9 Premature death from the third larval to pupal stages was reported in D. melanogaster mutants. 10,49 Finally, dauer formation is abnormal in Caenorhabditis elegans autophagy mutants.…”
Section: Developmentmentioning
confidence: 99%
“…The critical role played by autophagy in maintaining viability during starvation has been shown in Sacharomyces cerevisiae, 8 Dictyostelium discoideum 9 and Drosophila melanogaster. 10 In addition, we recently revealed that autophagy is also quite important to help mammals survive a unique period of starvation, the birthing process.…”
Section: Introductionmentioning
confidence: 99%
“…Unicellular organisms, such as yeast (S. cerevisiae and S. pombe) and ameba (D. discoideum) activate adaptive processes in nutrient poor conditions that result in sporulation or the generation of fruiting bodies, respectively. During these processes, autophagy recycles amino acids needed for de novo protein synthesis and increases the organism's chance of survival [57,58]. Also C. elegans uses autophagy to adapt to stressful conditions [59].…”
Section: Autophagy In Development and Differentiationmentioning
confidence: 99%
“…Mutations in the Dictyostelium autophagy gene orthologues ATG5, ATG6, ATG7 and ATG8 have subtle effects on growth in the presence of nutrients, but survival during nitrogen starvation is severely reduced. 16,17 Loss-of-function mutations in ATG genes in plants reduce tolerance to nitrogen or carbon depletion, resulting in enhanced chlorosis, reduced seed set, accelerated leaf senescence and limited lateral root elongation. [18][19][20] Autophagy is rapidly induced during exposure of Arabidopsis seedlings to oxidative stress.…”
Section: Autophagy In Cell Survivalmentioning
confidence: 99%